Zinc supplementation and ractopamine hydrochloride impact gene expression of zinc transporters in finishing beef steers - Rients, Emma L.; Wyatt, Remy N.; Deters, Erin L.; Genther-Schroeder, Olivia N.; Hansen, Stephanie L. (Frontiers in Animal Science, 2023)
Zinc is a trace mineral of interest for optimizing growth in feedlot cattle due to its roles in many physiological functions, including growth. Twenty-four Angus-cross steers (467 ± 13 kg) were used to assess the effects of supplemental Zn and ractopamine hydrochloride (RAC) on trace mineral concentrations and muscle gene expression. Four GrowSafe-equipped pens were randomly assigned to treatments (1 pen of six steers/treatment): 0 (CON), 60 (LOW), 120 (MED) or 180 (HI) mg supplemental Zn/kg DM (Availa-Zn, Zinpro). Dietary Zn treatments were initiated on d 0 and RAC supplementation (300 mg·steer·-1·d-1; Actogain45, Zoetis) began on d 53. Blood, liver and muscle (longissimus thoracis) samples were collected from all steers on d -4, 48, and 67. The LOW treatment was removed from gene expression analyses due to < 3 steers being represented for 14 of 22 genes. Data were analyzed using ProcMixed of SAS with the fixed effect of treatment and steer as the experimental unit; orthogonal linear and quadratic contrast statements were used to compare treatments. On d 48 and 67, there were linear and quadratic trends for plasma Zn to be greater in Zn-supplemented steers than CON (P ≤ 0.10). On d 48, there was a tendency for a quadratic decrease on the expression of SLC30A4 (P ≤ 0.07) but no other differences due to treatment. On d 67, several genes involved in Zn transport and storage (MTA1, SLC39A7, SLC39A8, SLC39A9, SLC39A10, SLC39A13) were decreased (P ≤ 0.08), suggesting increased growth influences intracellular Zn trafficking and demands.